Modularity in the trilobite head consistent with the hypothesized segmental origin of the eyes. Issue 6 (16th September 2022) - Vargas‐Parra, Ernesto E.; Hopkins, Melanie J.
Abstract: The trilobite head served multiple functions and was composed of several fused segments. Yet, the underlying organization of the trilobite head, and whether patterns are conserved across trilobites, remains unclear. Modeling the head as being composed of modules, or subunits that vary and thus have the potential to evolve semi‐independently can reveal underlying patterns of organization. Hypotheses of modular organization based on the comparative developmental biology of arthropods were evaluated using geometric morphometrics. Two‐dimensional (semi)landmark datasets collected from the cranidia of two Ordovician trilobite species, Calyptaulax annulata (Phacopida) and Cloacaspis senilis (Olenida sensu Adrain, 2011) were analyzed. The degree and pattern of modularity were assessed using the covariance ratio (CR), which compares the covariation within putative modules to the covariation between them, and the fit of different models was compared using an effect size measure derived from the CR. When treating the eyes as a distinct module, the best modular hypothesis identified for C. annulata shows the eyes and anteriormost region of the head integrated as a single module. The best modular hypotheses for C. senilis are more complex but the eyes still covary mostly strongly with the anterior part of the head. The latter is also the case for all other well‐supported models for both species. These results can be interpreted as a developmental signal corresponding to the anteriormost ocular segment of early arthropods that is retained throughout development, despite any likely selective pressures related to functional needs. Abstract : The degree and structure of modularity in the heads of two trilobite species, Calyptaulax annulata (left) and Cloacaspis senilis (right) are identified. Best fit hypotheses of modularity are consistent for both species: the eyes and anterior head highly covary (red), consistent with the anteriormost ocular segment of early arthropods. The pattern of modularity represents a developmental signal that remained detectable into adulthood. Research highlights: Degree and structure of modularity are identified in two trilobite species. In both species, the eyes and anteriormost head highly covary. Interpreted as a developmental signal corresponding to the ocular segment of early arthropods.